2021
DOI: 10.24952/ee.v8i2.3239
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Motivation in Learning English

Abstract: This study is to explore the students’ motivation in learning English. The kind of the research is quantitative research. The writer presented 40 items of questionnaire. Population of this research were the students at the sixth semester of English Department IAIN Padangsidimpuan (112) and the samples were 28 respondents that is taken by simple random sampling technique. The research is done by online. The data were taken by Google-Form or questionnaires trough Whats-App Group. Based on calculating the data, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A lack of practical application and difficulty comprehending concepts are factors that can impede the learning process [1]. A study found that the students' level of motivation to learn English was rated as moderate [5].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of practical application and difficulty comprehending concepts are factors that can impede the learning process [1]. A study found that the students' level of motivation to learn English was rated as moderate [5].…”
Section: Introductionmentioning
confidence: 99%
“…The problems that will be researched are implementation, planning, process and evaluation [12], [13], [14] of Blended Learning using Android Application in learning. Specific objectives of this research use Android application media which is very easy to use in order to find out students' achievement or learning outcomes.…”
Section: Introductionmentioning
confidence: 99%